Six‐year follow‐up of a case series with non‐communicating syringomyelia in multiple sclerosis. Issue 3 (17th December 2012) - Weier, K.; Naegelin, Y.; Amann, M.; Magon, S.; Mueller‐Lenke, N.; Radue, E.‐W.; Kappos, L.; Stippich, C.; Gass, A.; Sprenger, T.
Abstract : Background: Non‐communicating syringomyelia (NCS) has occasionally been described in case reports and small case series as an incidental finding of spinal cord (SC) pathology in patients with multiple sclerosis (MS), but only little is known on the clinical course and progression of NCS, and in more general terms on the prognosis of patients with MS and NCS. Methods: Nine patients with MS with known NCS at baseline and a control group of 18 age‐, sex‐ and disease course‐matched patients with MS without NCS were recruited for a follow‐up visit after 6 years. All 27 patients underwent clinical examination and brain magnetic resonance imaging (MRI), and 8/9 patients with NCS were additionally studied with MRI of the SC. MRI data were analysed for changes in length and maximal cross‐sectional area of the NCS, lesion volumes of the brain and cord as well as for volumetric metrics of the whole brain (using SIENAX), the cerebellum and medulla oblongata (using ECCET). Results: NCS did not significantly change in size when corrected for multiple comparisons. The clinical data (annual relapse rate, EDSS and disease duration) and MRI metrics (T2 and T1 lesion load; whole brain, cerebellar and medulla oblongata volumes as well as their percentage volume change per year) did not significantly differ between patients with MS with or without NCS. Conclusion: The stable findings regarding size and shape of the syrinx and lack of distinguishing MRI and clinical features support the assumption that NCS is not defining a prognostically or pathogenetically distinct subgroup of patients with MS.